Wakaf sebagai Pilar Ekonomi Syariah : Analisis Tata Kelola dan Penguatan Kelembagaan di Indonesia - Lafreda Nanda Wibowo; Talitha Al-Fadillah; Irene Anjani Hariyono; Daffa Abyan Pradana; Ade Nur Rohim (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
Waqf holds a crucial position in promoting social welfare and fostering the growth of a Sharia-based economy. In Indonesia, the success of waqf initiatives largely relies on sound governance and the operational effectiveness of waqf institutions. This study explores the roles of the Indonesian Waqf Board (BWI) as the regulatory authority and nazhir as the managers of waqf assets, while also highlighting key challenges such as technological limitations, lack of transparency, and weak supervision mechanisms. To overcome these obstacles, strategies including nazhir capacity building, digitalization of waqf management, and the application of the Waqf Core Principles Implementation Index (IIWCP) have been introduced. The findings suggest that adopting professional and innovative governance practices significantly enhances transparency, accountability, and the overall impact of waqf on social welfare and sustainable economic development.